Migrant and Refugee Youth’s Sexual and Reproductive Health and Rights: A Scoping Review to Inform Policies and Programs - Michaels Aibangbee; Sowbhagya Micheal; Sowbhagya Micheal; Virginia Mapedzahama; Pranee Liamputtong; Rashmi Pithavadian; Zakia Hossain; Elias Mpofu; Elias Mpofu; Elias Mpofu; Elias Mpofu; Tinashe Dune; et al. (International Journal of Public Health, 2023)
Objectives: Migrants and refugee youth (MRY) in Western nations are less likely to participate in sexual reproductive health (SRH) services. Consequently, MRY are more likely to encounter adverse SRH experiences due to limited access to and knowledge of SRH services. A scoping review was conducted to examine MRY’s understanding of and the implications for inclusive sexual and reproductive health and rights (SRHR) programs and policies.Methods: A systematic search of literature across seven academic databases was conducted. Data were extracted following Partners for Dignity and Rights’ Human Rights Assessment framework and analysed using the thematic-synthesis method.Results: 38 literature (peer-reviewed, 24 and grey, 14) were considered eligible for inclusion. The findings highlighted significant barriers and the under-implementation of SRHR support and services by MRY. Key policy implications include a need for programs to support MRY’s SRHR education, diversity, equity and inclusiveness and privacy protections.Conclusion: The review shows that the emerging evidence on MRY SRHR suggests gaps in practices for resourcing policies and programs that promote sustainable SRH for vulnerable populations. Policies for MRY’s SRHR should prioritise programs that focus on diversity, equity and inclusion with targeted education and community resourcing strategies for sustainability.